1995
DOI: 10.1016/0042-6989(95)00050-a
|View full text |Cite
|
Sign up to set email alerts
|

Shape from shaded random surfaces

Abstract: The perception of surface relief from random shading patterns is measured by having observers adjust three-dimensional local probes, the projections of which are superimposed on the image. Three observers perform four settings of 91 probes on each of 14 images. These images are generated by calculating the Lambertian reflectance of a random superposition of elliptical Gaussian hills and valleys illuminated by a single distant light source as well as by ambient light. Neither the surface reflectance equation no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…In images of materials, the 3-D structure of a surface is mainly conveyed by shape from shading. Many algorithms for the recovery of 3-D shape from shading cues have been proposed in the computational literature (Breton & Zucker, 1996;Horn, 1970: Ikeuchi & Horn, 1981Pentland, 1982), and a few studies have investigated human performance in recovery of object shape (De Haan, Erens, & Noest, 1995;Erens, Kappers, & Koenderink, 1993), but none have studied Giesel, M., & Zaidi, Q. (2013).…”
Section: Introductionmentioning
confidence: 99%
“…In images of materials, the 3-D structure of a surface is mainly conveyed by shape from shading. Many algorithms for the recovery of 3-D shape from shading cues have been proposed in the computational literature (Breton & Zucker, 1996;Horn, 1970: Ikeuchi & Horn, 1981Pentland, 1982), and a few studies have investigated human performance in recovery of object shape (De Haan, Erens, & Noest, 1995;Erens, Kappers, & Koenderink, 1993), but none have studied Giesel, M., & Zaidi, Q. (2013).…”
Section: Introductionmentioning
confidence: 99%
“…There is an evidence that the pictorial relief, i.e., the imaginary relief extracted from a 2D projection of a 3D scene, such as a rendering or a photograph, is systematically distorted relative to the actual structure of the observed scene [7,34]. The variations among observers' judgments were revealed to be complex and thus could not be accounted for by a simple depth scaling transformation.…”
Section: Perception Of Surfacesmentioning
confidence: 98%
“…Cole et al showed that certain shape cues can be extracted solely from important lines, even though shape cues from shaded images are more accurate [6]. However, shading alone cannot yield the depth structure of a scene correctly [7]. The depth cues from shading are poor when compared to the retinal disparity (stereopsis) and kinetic cues [14].…”
Section: Perception Of Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…(c) Relative proportion of the accuracy variance in the total variance for each stimulus condition. Noest, 1995;Koenderink & van Doorn, 1992;Todd, Oomes, Koenderink, & Kappers, 2004). To test for this effect and further potential differences between the stimulus conditions, we reparametrized the normals indicated by the gauge figure in terms of spherical slant and tilt coordinates (see Figure 14a).…”
Section: Local Slant and Tilt Errorsmentioning
confidence: 99%